Analysis of cloud authentication systems for biometric data - Assylbek, D. O. (Харківський національний автомобільно-дорожній універститет, 2024)
This article analyzes cloud authentication systems that use biometric data to enhance security. Cloud technologies enable efficient management of biometric data, providing high security and user convenience. However, these systems face challenges related to data storage security, privacy, and infrastructure reliability.
Keywords: Cloud; Biometric Data; Authentication; Security; Privacy; Scalability; Financial Transactions; Encryption